2013
DOI: 10.1002/pc.22734
|View full text |Cite
|
Sign up to set email alerts
|

A review on electrically conductive polypropylene and polyethylene

Abstract: Conductive plastics are new generation functional materials with potential application in electronics, space and aviation industries. Polypropylene (PP) and polyethylene (PE) being most common, widely available and cheapest thermoplastic, if made conductive, can be revolutionary in the field of engineering thermoplastics. The article deals with the fabrication of electrically conductive PP and PE for electromagnetic interference/ radio frequency (EMI/RF) shielding applications and protection against electrosta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
63
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(68 citation statements)
references
References 113 publications
(131 reference statements)
5
63
0
Order By: Relevance
“…In both graphs, through-thickness direction (filled squares) and in-plane direction (empty squares) are represented. First of all, as it is reported in literature [14,15], it can be observed that the electrical percolation threshold of EG and CB composites can be found at higher content of filler if compared with MWCNTs. However, the most interesting outcome shown in Figure 1 is related to the comparison of the electrical percolation threshold in the through-thickness direction with the in-plane one.…”
Section: Methodssupporting
confidence: 57%
“…In both graphs, through-thickness direction (filled squares) and in-plane direction (empty squares) are represented. First of all, as it is reported in literature [14,15], it can be observed that the electrical percolation threshold of EG and CB composites can be found at higher content of filler if compared with MWCNTs. However, the most interesting outcome shown in Figure 1 is related to the comparison of the electrical percolation threshold in the through-thickness direction with the in-plane one.…”
Section: Methodssupporting
confidence: 57%
“…10b) shows a net jump from 50 pF to a saturation value close to 95 pF beyond the critical concentration of 10 % of cellulose fiber concentration. Although a percolation phenomenon in electrically percolative polymer-based composites involves a sudden change of several orders of magnitude [54,55], Fig. 10 clearly indicates that something like a percolation effect occurs beyond 10 % of cellulose fiber content.…”
Section: Electrical Properties Of the Compositementioning
confidence: 97%
“…Addition of nanoparticles as fillers in the polymer matrix not only improves the polymer strength, rigidity, and flexibility, but also facilitates the improvement of the polymer light transmission, barrier property, thermal resistance and electrical conductivity [1][2][3][4]. Several nanoparticles have been used as fillers in the polymer matrix so as to achieve the aforesaid functionalities of polymer nanocomposites.…”
Section: Introductionmentioning
confidence: 98%